2017
DOI: 10.36002/jkt.v1i2.270
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Berhubungan Dengan Keluhan Kelelahan Mata Pada Pekerja Pengguna Komputer Di Bank X Kota Bangko

Abstract: ABSTRAK<br />Hasil  dari  Riset  Kesehatan  Dasar  tahun  2013  menunjukkan   bahwa  di Indonesia prevalensi severe<br />low vision atau kerusakan fungsi penglihatan dan mempunyai tajam penglihatan kurang dari 6/18 pada umur<br />produktif (15-54 tahun) sebesar 1,49% dan prevalensi kebutaan sebesar 0,5%. Prevalensi severe low vision<br />dan kebutaan meningkat pesat pada penduduk sekitar dua sampai tiga kali lipat setiap 10 tahun.Penelitian ini<br />bertujuan untuk mengetahui fakt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
1
3
0
9
Order By: Relevance
“…The chi square statistical test results are known at 5% degrees obtained by Pvalue = 0.245 or (p> 0.05) then the null hypothesis (Ho) is accepted and the alternative hypothesis (Ha) is rejected so it can be concluded that the distance of the monitor with eye fatigue does not have a meaningful relationship. This research is in line with Berliana & Rahmayanti, (2017), which states that there is a relationship between monitor distance and eye fatigue (p value 0.000). Ergonomic distance between non-ergonomic ones will risk causing eye fatigue.…”
Section: Resultssupporting
confidence: 90%
“…The chi square statistical test results are known at 5% degrees obtained by Pvalue = 0.245 or (p> 0.05) then the null hypothesis (Ho) is accepted and the alternative hypothesis (Ha) is rejected so it can be concluded that the distance of the monitor with eye fatigue does not have a meaningful relationship. This research is in line with Berliana & Rahmayanti, (2017), which states that there is a relationship between monitor distance and eye fatigue (p value 0.000). Ergonomic distance between non-ergonomic ones will risk causing eye fatigue.…”
Section: Resultssupporting
confidence: 90%
“…19 The longer user interacts with the monitor screen, the physiological abilities of the muscles and the muscles around the eyes will decrease; as a result, the eyes will experience fatigue. 20 p-ISSN 2407-0505…”
Section: Discussionmentioning
confidence: 99%
“…6 The results of Irma, Lestari, and Kurniawan's research (2019) on computer users at PT PLN (Persero) Rayon Soppeng and Rayon Pajalesang Soppeng Regency, it was found that there was a correlation between monitor distance, age, and duration of computer use with subjective complaints of eye fatigue in computer users. 7 Rathore (2017) also states that workers who work with computers for more than 3 hours per day are more at risk of eye fatigue complaints. 8 In addition to prolonged computer use, lighting conditions that are too dark or too bright cause a decrease in contrast so that in dark conditions, accommodation of the eyes occurs more often and can trigger eye fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Jika tidak segera dilakukan pencegahan maka akan berakibat pada menurunnya tingkat ketajaman penglihatan. Keluhan kelelahan tersebut akan bertambah menjadi sakit kepala (14). Gejala CVS yang paling banyak dikeluhkan oleh pegawai yaitu sakit kepala sebanyak 75,61% (62 orang) dan gejala yang paling sedikit dikeluhkan pegawai yaitu merasakan sensasi benda asing dalam mata yaitu sebanyak 35,37% (29 orang).…”
Section: Hubungan Pemeriksaan Refraksi Mata Dengan Kejadian Cvs Pada ...unclassified